Four new HLA alleles, HLA‐A*02:912, ‐B*15:557, ‐B*15:558, and ‐B*40:97, identified in the Chinese Han population. (4th March 2020) - Zhang, Xinwen; Wang, Yanpeng; Shi, Li; Yao, Yufeng; Dai, Shuying
Abstract : The new HLA‐A*02:912, ‐B*15:557, ‐B*15:558, and ‐B*40:97 alleles in Chinese Han.